Not disabled: just differently abled - Othman, Muhammad Lukman; Iskandar, Muhammad Danial; Hasnawi, Nur Alya Mysara; Mohd Fauzi, Nadzatul Nabihah; Muhammad Fadli, Durratul Hanan; Mohamad Safar, Nur Ainul Nadia; Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association (MIMPA), 2023)
This e-book is based on the topic of disability and accessibility for people with disabilities. It touches on three main types of impairments namely of mobility, hearing and vision. It also describes disability etiquettes and Islamic views on disabilities.